(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents an automatic mesh generation scheme for a linear convex polygonal domain in with boundary composed of piecewise straight lines.We can express = in which is a polygonal domain of N oriented edges with end points and . Where,it is assumed that can be discretised into a set of N triangles, and we can also divide each triangle into smaller triangles so that which gives us a triangular mesh with h-refinement ,when this procedure is repeated for all triangles we obtain a triangular mesh with h-refinement for a linear convex polygon, further we can discretise each triangle into three special quadrilaterals a=0,1,2 which are obtained by joining the centroid to the midpoint of its sides and we have created an all quadrilateral mesh. We choose = an arbitrary triangle with vertices in Cartesian space We have furthered refined this mesh two times. We have taken this further and created 12-new quadrilaterals by joining the centroids of the 3-special quadrilaterals to the midpoints which can be called as first h-refinement.Then each of these quadrilateral is divided into four smaller quadrilaterals again by joining the centroids to the mid points of sides which we call as the second h- refinement.